2018
DOI: 10.1038/s41377-018-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength stability in a hybrid photonic crystal laser through controlled nonlinear absorptive heating in the reflector

Abstract: The need for miniaturized, fully integrated semiconductor lasers has stimulated significant research efforts into realizing unconventional configurations that can meet the performance requirements of a large spectrum of applications, ranging from communication systems to sensing. We demonstrate a hybrid, silicon  photonics-compatible photonic crystal (PhC) laser architecture that can be used to implement cost-effective, high-capacity light sources, with high side-mode suppression ratio and milliwatt output out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…It is found that photoexcitation dynamically modulates the conductivity of the graphene sheet in the sample with decay of 2.79 ps, resulting in absorption tuning on the order of 40%. The time scale is comparable and even smaller with respect to other emerging or established platforms; 30 32 that is, a germanium-based metasurface with a full recovery time of 17 ps has been recently demonstrated. 31 Our system holds additionally the advantage of the 2D nature of the material, which is ideal for the realization of minimized components.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that photoexcitation dynamically modulates the conductivity of the graphene sheet in the sample with decay of 2.79 ps, resulting in absorption tuning on the order of 40%. The time scale is comparable and even smaller with respect to other emerging or established platforms; 30 32 that is, a germanium-based metasurface with a full recovery time of 17 ps has been recently demonstrated. 31 Our system holds additionally the advantage of the 2D nature of the material, which is ideal for the realization of minimized components.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in light confinement at the wavelength scale are leading to smaller and smaller high-performance resonators fabricated on silicon-on-insulator platforms. Specifically, spherical cavities [6], toroidal cavities [7,8], and photonic crystal (PhC) cavities [9][10][11][12][13][14] offer very low optical losses [i.e., high quality (Q) factors [15]], low coupling losses [16], and small mode volumes in the range of λ 3 , and enable the investigation of cavity quantum electrodynamics [17], all-optical computing [18], lasing and parametric oscillations [19][20][21], and enhanced nonlinear processes [22,23]. The wavelength scale confinement of light in microcavities leads to a huge enhancement of the relatively small optical nonlinearities of silicon [24].…”
Section: Introductionmentioning
confidence: 99%
“…Full butt-coupling and accurate vertical alignment makes mode matching between the laser and the polymer waveguide easier compared to printing the laser at the top of the SOI and adjust the thickness of the polymer to align the waveguides. The polymer waveguide can act as an optical link to other optical functions of a photonic circuit or it can be used to evanescently couple the light to a tapered SOI waveguide for hybrid polymer-SOI photonics [35] or to realize advanced lasers [6]. The configuration allows the recess facet to be positioned far from the tip of the SOI taper, preventing damaging the taper during the etch process.…”
Section: A Layoutmentioning
confidence: 99%
“…Mode mismatch is the major source of the insertion losses in edge-coupling, which is overcome by the use of mode size converters (MSC) and tight alignment tolerances. Reflective semiconductor optical amplifier (RSOA) chips have been edge-coupled to silicon photonics in external cavity laser configuration, with no need of MSC nor wafer bonding but still needing precise alignment [5], [6]. The edge coupling of fully packaged lasers on chip has been reported [7]- [10].…”
Section: Introductionmentioning
confidence: 99%